Bibliographic guide to Chicana and Latina narrative - Leonard, Kathy S., 1952- (Bibliographies and indexes in women's studies, 2003)
There has been a dramatic increase in the amount of narrative work published by Chicana and Latina authors in the past 5 to 10 years. Nonetheless, there has been little attempt to catalog this material. This reference provides convenient access to all forms of narrative written by Chicana and Latina authors from the early 1940s through 2002. In doing so, it helps users locate these works and surveys the growth of this vast body of literature.